2021
DOI: 10.3390/fishes6040082
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences and Pathogenicity Analysis of Two Red Sea Bream Iridoviruses Isolated from Cultured Fish in Korea

Abstract: In Korea, red sea bream iridovirus (RSIV), especially subtype II, has been the main causative agent of red sea bream iridoviral disease since the 1990s. Herein, we report two Korean RSIV isolates with different subtypes based on the major capsid protein and adenosine triphosphatase genes: 17SbTy (RSIV mixed subtype I/II) from Japanese seabass (Lateolabrax japonicus) and 17RbGs (RSIV subtype II) from rock bream (Oplegnathus fasciatus). The complete genome sequences of 17SbTy and 17RbGs were 112,360 and 112,235 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…RSIV is a double‐stranded DNA virus that belongs to the family Iridoviridae and the genus Megalocytivirus . The length of RSIV genome is ~112 kbp, and the RSIV whole‐genome sequence was first reported in 2002 in an isolate from Ehime Prefecture, Japan (Kurita et al, 2002), after which other genomic sequences of isolates in India (Puneeth et al, 2021) and Korea (Jeong et al, 2021) were continuously reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RSIV is a double‐stranded DNA virus that belongs to the family Iridoviridae and the genus Megalocytivirus . The length of RSIV genome is ~112 kbp, and the RSIV whole‐genome sequence was first reported in 2002 in an isolate from Ehime Prefecture, Japan (Kurita et al, 2002), after which other genomic sequences of isolates in India (Puneeth et al, 2021) and Korea (Jeong et al, 2021) were continuously reported.…”
Section: Introductionmentioning
confidence: 99%
“…AP017456.1), can be used for more detailed classification of the RSIV group of megalocytiviruses (Sakseepipad et al, 2021). As the genome sequences of RSIV were analysed, Jeong et al (2021) discovered mutations that may affect viral virulence on protein‐coding regions of two RSIV isolated in Korea in 2017 compared with each other and previously reported RSIV genomes.…”
Section: Introductionmentioning
confidence: 99%
“…Various fish viruses were inoculated into DGF cells to evaluate their susceptibility to viruses. The viruses used in this experiment are as follows: red sea bream iridovirus (RSIV, 17RbGs strain; isolated from rock bream; [ 25 ]), infectious spleen and kidney necrosis virus (ISKNV, PGIV strain; isolated from pearl gourami; [ 7 ]), viral hemorrhagic septicemia virus (VHSV; isolated from olive flounder; [ 26 ]), hirame rhabdovirus (HIRRV; ATCC, VR-1391), and spring viraemia of carp virus (SVCV, SVCV-K1 strain; isolated from common crap; [ 27 ]); nervous necrosis virus (NNV, RGNNV-type; isolated from sea bass; [ 26 ]). The infectivity titer of the virus was measured by TCID 50 assay using DGF, epithelioma papulosum cyprini (EPC), and E11 cell lines for megalocytiviruses (RSIV and ISKNV), rhabdoviruses (VHSV, HIRRV, and SVCV), and NNV, respectively.…”
Section: Methodsmentioning
confidence: 99%